Wired to Connect: The Autonomic Socioemotional Reflex Arc - Ludwig, Robert J.; Welch, Martha G. (Frontiers in Psychology, 2022)
We propose that mothers and infants are biologically designed to co-regulate one another’s autonomic state through an autonomic conditioning process, which starts during gestation and results in the formation of an interpersonal autonomic socioemotional reflex (ASR). Theoretically, the ASR behaviors reflect the autonomic physiology that is driving the behavior. Therefore, the ASR can be used to monitor the health of the mother/infant autonomic relationship. In randomized controlled trials among mothers of preterm infants at 4 months, we have shown ASR behaviors are measurable and that they correlate with autonomic physiology. In addition, using multiple behavioral and physiology measures we have demonstrated that an intervention based on autonomic conditioning theory changes the mother/infant autonomic physiology and their emotional relationship. Here, we consider the problem of how mother/infant socioemotional sensory stimuli co-regulate physiology and behavior without the benefit of the thalamus, amygdala or cortex. We begin with a 500-year review of reflex arc theory, which considers the wiring or signaling pathway between sensory stimulus and emotional behavior. We highlight findings over the past 15 years that support our contention that mother/infant socioemotional behavior is driven by their mutual autonomic states, as opposed to individual cortical fixed traits. We review our findings from randomized controlled trials testing an intervention in preterm infants and mothers that support our theory, as well as our findings on oxytocin cell signaling. Finally, we discuss the significance of our theory for the treatment of mothers and infants with socioemotional disorders.